2013
DOI: 10.1371/journal.pone.0057392
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Clinical and Experimental Characteristics in the Patients Younger than 60 Years Old with Myelodysplastic Syndromes

Abstract: Myelodysplastic syndromes (MDS) mainly occur in elderly individuals in Western countries. However, MDS is commonly found in young individuals (<60 years) in Asia. The reason for the high incidence in younger individuals is still unclear, and the differences in disease features between young and elderly patients with MDS have been not well recognized. To explore these issues, in this study, we analyzed the clinical and experimental characteristics of MDS in the patients younger and older than 60 years old and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
7
9
0
Order By: Relevance
“…Hence our patients were segregated into two cohorts using the cut-off age of 60 years depending on UN and WHO recommendations 22,23 . The result highlighted that prognosis was more favorable in younger patients compared with older ones which is consistent with other reports 17,18,20 . The disparity in survival largely resulted from the elderly's comorbidities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Hence our patients were segregated into two cohorts using the cut-off age of 60 years depending on UN and WHO recommendations 22,23 . The result highlighted that prognosis was more favorable in younger patients compared with older ones which is consistent with other reports 17,18,20 . The disparity in survival largely resulted from the elderly's comorbidities.…”
Section: Discussionsupporting
confidence: 92%
“…Although Kuendgen et al 18 held the view that younger MDS patients were not signi cantly different compared with older ones. Other studies indicated that younger patients with MDS represented unique clinical and biological features and different prognosis 17,[19][20][21] . Therefore, we expanded our analyses to nd whether the genomic-clinical risk model derived from older patients had different performance in different age cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The respective indices for septuagenarians were 16.57 (14.17–19.37) vs. 3.57 (2.73–4.68) and 39.47 (35.67–43.68) vs. 18.88 (16.79–21.22) translating into ratios 4.64 and 2.09, and for octogenarians and older 28.63 (24.03–34.11) vs. 6.16 (4.8–7.9) and 88.41 (80.01–97.68) vs. 19.87 (17.3–22.82), translating to ratios 4.65 and 4.45. Interestingly, in younger patients, prevalence rates were higher in females, which stays in line with other reports focusing on younger patients, mostly under 50 yr of age .…”
Section: Methodssupporting
confidence: 91%
“…By contrast, the median age in China and Japan is earlier than that of Western countries, ranging from 62–76 years old [ 17 , 18 ]. Punctually, a median age of 57 years old has been once reported in a Chinese study [ 21 ], and another Chinese report from 2013 showed that over half of the patients with MDS (61.9%) were younger than 60 year-old at the first diagnosis [ 22 ]. By contrast, about 10% of the patients were younger than 50 years of age in a German study from 2011 [ 23 ].…”
Section: Resultsmentioning
confidence: 99%